Fundamental care for people with cognitive impairment in the hospital setting: A study combining positive organisational scholarship and video‐reflexive ethnography. Issue 11 (7th October 2019) - Collier, Aileen; De Bellis, Anita; Hosie, Annmarie; Dadich, Ann; Symonds, Tamsin; Prendergast, Justin; Rodrigues, Jade; Bevan, Alan
Abstract: Aims and objectives: To clarify how high‐quality fundamentals of care for people with dementia and/or delirium were practised in a specialist geriatric evaluation and management unit. Background: Older people with cognitive impairment represent a significant number of people who are admitted to hospital. They are at increased risk of dying, readmission and long hospital stays, relative to those without cognitive impairment. There is an urgent need to elucidate the conditions that underpin safe and high‐quality fundamental care for these patients and their families. Methods: Using the innovative methodologies of positive organisational scholarship in healthcare and video‐reflexive ethnography, this 18‐month study was conducted within an inpatient geriatric evaluation and management unit for people with dementia and/or delirium in South Australia. Patients, family members and staff members (managerial, clinical and nonclinical) participated by allowing researchers to document ethnographic fieldwork notes and film their practices and/or accounts thereof; and/or interpreting digital recordings with researchers in order to make sense of data in a process of co‐analysis. This study is reported using Standards for Reporting Qualitative Research reporting guidelines. Results: High‐quality fundamental care for people with dementia and/or delirium in hospital and their families was associated with the special space of the hospital unit; an aptitude for people with dementia; a capacity to translate person‐centred fundamentals of care from rhetoric to reality; and an appreciation for teamwork. Conclusion: This study clarified how teams working in hospital can practise high‐quality fundamentals of care for older people with dementia and/or delirium. Delivery of high‐quality fundamental care in this setting was dependent, not only on nurses, but the entire ward team working cohesively in a "weave of commitment." Relevance to clinical practice: Efforts to improve fundamental care for people with cognitive impairment need to encompass values and philosophy of person‐centred care, including the contributions by all staff to care delivery.